PERANCANGAN SISTEM INFORMASI PENJUALAN TIKET KAPAL BERBASIS WEB STUDI KASUS SB RAHMAT JAYA - Sitinjak, Judika Bestian; Andema, Henky (JUTEKDISI, 2024)
Currently the use of internet services as a means to obtain information is increasingly being used. Because of its wide reach, the internet is ideal when used as a means of promotion and means of publishing information. The purpose of making this web program is to promote the company while providing services to customers regarding on-line ticket bookings. The internet is a very potential medium for developing a dynamic and wide-scale information system, with the internet information about anything can be obtained easily and quickly. Based on the various conveniences and uses that the internet has, a "On-Line Ship Ticket Booking System" has been developed. On-Line Ticket Ordering System. This Web-based is made with PHP, MySQL and Adobe Dreamweaver CS5 software. This information system is designed to provide convenience in terms of ticket ordering services and obtaining other information needed by customers, especially for SB Rahmat Jaya services.